Beyond Pairwise Interactions: Higher-Order Q-Analysis of fMRI-Based Brain Functional Networks in Patients With Major Depressive Disorder - Semen A. Kurkin; Nikita M. Smirnov; Rositsa Paunova; Sevdalina Kandilarova; Drozdstoy Stoyanov; Larisa Mayorova; Alexander E. Hramov (IEEE Access)
Major depressive disorder (MDD) is associated with complex disruptions in brain function, yet the underlying neural mechanisms remain incompletely understood. Traditional approaches to studying functional brain networks have primarily focused on pairwise interactions between brain regions, offering valuable insights into basic connectivity. However, such methods often fail to capture the complexity of higher-order interactions that are critical for understanding integrative processes in the brain. This study aims to address this gap by applying Q-analysis, a mathematical framework that extends beyond pairwise interactions, to fMRI-derived brain networks to investigate higher-order interactions and structural organization in individuals with MDD compared to healthy controls (HCs). Our analysis revealed significant alterations in the topology of brain networks in MDD patients, characterized by a lower maximum topology level and an increased prevalence of isolated edges and chains at the pairwise interaction level. The substantia nigra area demonstrated a higher topological dimension in MDD, suggesting its greater integration into disrupted network structures, potentially reflecting dopaminergic dysfunction associated with the disorder. Additionally, the consensus networks at higher topology levels indicated distinct network configurations between MDD patients and HCs, with the former exhibiting a single q-connected component primarily involving limbic, cerebellar, and occipital-temporal regions. We identified significant disruptions in the higher-order organizational structures of the brain, characterized by reduced topological diversity and complexity, fewer and less connected cliques, and altered involvement of key brain regions in MDD: the increased engagement of the limbic structures such as the substantia nigra, parahippocampal gyrus, and hippocampus, and decreased involvement of the cerebellum, the occipital and temporal lobes. Our study introduces a novel approach to understanding MDD pathophysiology through the lens of higher-order network structures, offering potential avenues for more targeted diagnostic and therapeutic strategies.